Accuracy of 68Ga DOTANOC PET/CT Imaging in Patients With Multiple Endocrine Neoplasia Syndromes. (July 2015) - Sharma, Punit; Mukherjee, Anirban; Karunanithi, Sellam; Naswa, Niraj; Kumar, Rakesh; Ammini, Ariachery C.; Bal, Chandrasekhar
Abstract : Objective: The aim of this study was to evaluate the role of 68 Ga DOTANOC PET/CT imaging in patients with multiple endocrine neoplasia (MEN) syndromes. Patients and Methods: Data of 33 patients (age, 33.5 [13.8] years; male 14/female 19) with MEN syndromes (MEN 1, 9; MEN 2A, 19; MEN 2B, 5) who underwent 41 68 Ga DOTANOC PET/CT studies were retrospectively analyzed. Twenty PET/CTs were done for staging and 21 for restating. PET/CT images were evaluated in consensus by 2 nuclear medicine physicians, qualitatively and semiquantitatively (SUVmax ). A combination of histopathology, clinical, and biomarker follow-up was taken as reference standard. Results: Of the total 41 68 Ga DOTANOC PET/CTs, 34 were interpreted as positive for neuroendocrine tumors (NETs) and 7 as negative. The patientwise sensitivity of PET/CT was 94% (95% confidence interval [CI], 80–99), specificity was 71% (95% CI, 29–96), positive predictive value was 94% (95% CI, 80–99), negative predictive value was 71% (95% CI, 29–96), and accuracy was 90%. A total of 74 disease sites were demonstrated on PET/CT, including 41 primary NETs (pancreas, 10; stomach, 2; pheochromocytoma, 10; medullary thyroid carcinoma, 19), 31 metastatic sites (lymph node, 15; liver, 10; bone, 4; lung, 1; breast, 1), and 2 parathyroid adenomas. Lesionwise sensitivity, positive predictive value, and accuracy of PET/CT were 93%, 96%, and 90% overall, 89%, 95%, and 85% for primary tumors, and 100%, 97%, and 97% for metastasis, respectively. Among primary tumors, the SUVmax of medullary thyroid carcinoma was significantly lower than gastro pancreatic NETs ( P = 0.003) and pheochromocytomas ( P = 0.003). No site-specific difference was seen in SUVmax of metastatic lesions. Conclusions: 68 Ga DOTANOC PET/CT shows high diagnostic accuracy in MEN syndrome and can demonstrate both primary and metastatic NETs in these patients.